USIA IBU SAAT HAMIL DAN KEJADIAN STUNTING PADA ANAK USIA 1-3 TAHUN - Tri Nurhidayati; Heny Rosiana; Rozikhan Rozikhan (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2020)
One of the nutritional problems at this time is the high stunting of child in under five yearsStunting caused by a multidimensional factor and not only caused by malnutritionexperienced by pregnant women and children under five. Other factors that affect the motherare the mother's posture (short), the pregnancy is too close, the mother is still a teenagerand the lack of nutritional intake during pregnancy. This study aims to analyze therelationship between the age of pregnant women and the incidence of stunting. This type oresearch is analytic observational with a case control design, the number of samples is 80respondents, namely mothers who have children aged 1-3 years (40 cases and 40 controls)Data analysis used univariate and bivariate analysis. Maternal age at pregnancy did nosignificantly influence the incidence of stunting p value 0.368. The conclusion is that themother's age at pregnancy hasn’t a risk of stunting in children who are born.